Genetic Diversity and Population Structure of the USDA Sweetpotato (Ipomoea batatas) Germplasm Collections Using GBSpoly - Wadl, Phillip A.; Olukolu, Bode A.; Branham, Sandra E.; Jarret, Robert L.; Yencho, G. Craig; Jackson, D. Michael (Frontiers in Plant Science, 2018)
Sweetpotato, Ipomoea batatas, plays a critical role in food security and is the third most important root crop worldwide following potatoes and cassava. Sweetpotato is an important crop in the United States (US) and is valued at over $700 million dollars annually. The sweetpotato germplasm collection of the US is maintained by the USDA, ARS, Plant Genetic Resources Conservation Unit and provides the genetic basis for sweetpotato crop improvement. To date, no genome-wide assessment of genetic diversity within this collection has been reported in the published literature. In our study, population structure and genetic diversity of 417 sweetpotato accessions originating from 8 broad geographical regions (Africa, Australia, Caribbean, Central America, Far East, North America, Pacific Islands, and South America) were determined using over 30,000 single nucleotide polymorphisms (SNPs) using a genotyping-by-sequencing (GBS) protocol optimized for highly heterozygous and polyploid species. Bayesian clustering analyses (STRUCTURE) grouped the accessions into four genetic groups (Central American, North American, South American, other regions) and indicated a high degree of mixed ancestry. A neighbor-joining cladogram, principal components analysis, and a genetic distance matrix of the accessions supported the population structure analysis. Pairwise FST values between broad geographical regions based on the origin of accessions ranged from 0.017 (Far East – Pacific Islands) to 0.110 (Australia – South America) and supported the clustering of accessions based on genetic distance. The markers developed for use with this collection of accessions provide an important genomic resource for the sweetpotato community, and contribute to our understanding of the genetic diversity present within the US sweetpotato collection and the species.